Interaction between estradiol and 5-HT1A receptors in the median raphe nucleus on acquisition of aversive information and association to the context in ovariectomized rats - Telma GonÃ§alves Carneiro Spera de Andrade; JoÃ£o Victor dos Santos Silva; Matheus Fitipaldi Batistela; Fernando Frei; Ana Beatriz SantâAna (Neurobiology of Stress, 2017)
The median raphe nucleus (MRN) is related to stress resistance and defensive responses, a crucial source of serotonergic neurons that project to prosencephalic structures related to stress and anxiety. Estrogen receptors were identified in this mesencephalic structure. It is possible that the estrogen action is related to serotonin effect on somatodendritic 5-HT1A receptors, inhibiting the function of serotonergic neurons and thus preventing of the stress effect and inducing anxiolysis. So, in order to evaluate these aspects, female Wistar rats were ovariectomized and 21 days later were given a direct microinjection of estradiol benzoate (EB) (1200 ng) into the MRN, preceded by microinjections of saline or WAY100.635 (100 ng), a 5-HT1A receptor antagonist. Immediately after the two microinjections, the ovariectomized rats were conditioned with an aversive event (foot shock) session in a Skinner box. Twenty-four hours later, they were exposed to the same context in a test session for 5 min for behavioral assessment: freezing, rearing, locomotion, grooming, and autonomic responses (fecal boluses and micturition). EB microinjection in the MRN prior to the exposure of animals to the foot shocks in the conditioning session did not alter their behavior in this session, but neutralized the association of the aversive experience to the context: there was a decrease in the expression of freezing and an increased rearing activity in the test session. This effect was reversed by prior microinjection of WAY100.635. In conclusion, EB acted on serotonergic neurons in the MRN of the ovariectomized rats, impairing the association of the aversive experience to the context, by co-modulating the functionality of somatodendritic 5-HT1A. Keywords: Contextual conditioning, Median raphe nucleus, Estradiol benzoate, 5-HT1A receptors, WAY100.635, Ovariectomized rats, Anxiety